A simple way to identify insulin resistance in non-diabetic acute coronary syndrome patients with impaired fasting glucose - Sayantan Ray; Ashit Kumar Bairagi; Santanu Guha; Satyabrata Ganguly; Debes Ray; Ashis Kumar Basu; Anirban Sinha (Indian Journal of Endocrinology and Metabolism, 2012)
Background and Objective: The incidence of coronary artery disease (CAD) is increasing in India. Recent data suggesting insulin resistance can predict cardiovascular disease independently of the other risk factors, such as hypertension, visceral obesity, or dyslipidemia, so a focus on the relation between acute coronary syndrome (ACS) and insulin resistance is relevant. Several studies addressing serum lipoprotein ratios as surrogates for insulin resistance have found promising results. We analyzed the association of lipoprotein ratios with the homeostatic model assessment of insulin resistance (HOMA-IR). Methods: One hundred non-diabetic patients with impaired fasting glucose admitted with a diagnosis of ACS were included in the study. Admission fasting glucose and insulin concentrations were measured. The HOMA-IR was used to calculate insulin resistance. The fasting serum total cholesterol (TC), triglycerides (TG), and high-density lipoprotein (HDL-C) levels are used to calculate following lipid ratios: TC/HDL-C and TG/HDL-C. The areas under the curves (AUC) of the receiver operating characteristic curves (ROC) were used to compare the power of these serum lipoprotein ratio markers. Results: Lipoprotein ratios were significantly higher in patients with HOMA Index >2 as compared to patients with Index <2. TG/HDL-C ratio and TC/HDL-C ratio were significantly correlated with HOMA-IR (P < 0.05) as obtained by Pearson′s correlation analysis (r = 0.4459, P = 0.0012; r = 0.4815, P = 0.0004; r = 0.3993; P = 0.0041, respectively). The area under the ROC curve of the TG/HDL-C and TC/HDL-C ratios for predicting insulin resistance was 0.80 (95% CI, 0.67-0.93), 0.78 (95% CI, 0.65-0.91), respectively. Conclusion: A plasma TG/HDL-C ratio and TC/HDL-C ratio provide a simple means of identifying insulin resistant and can be used as the markers of insulin resistance and cardiovascular diseases risk in adult non-diabetic patients.